A Prospective Multicenter Study of the Chinese Scoring System for Hepatitis B Liver Failure - Zhe-bin, Wu; Bing-liang, Lin; Liang, Peng; Zhi, Chen; Xin-xin, Zhang; De-ming, Tan; Wan-hua, Ren; Kai, Wang; Xue-bin, Yan; Wei-min, Ke; Yu-bao, Zheng; Zhi-liang, Gao (Frontiers in Medicine, 2021)
Objective: To evaluate the clinical utility of a Chinese scoring system for hepatitis B liver failure in a prospective and multicenter study. Methods: Clinical data for 1143 patients with hepatitis B liver failure who had been followed up for a minimum of 6 months were collected from seven liver disease centers across China. The disease severity and prognosis for the patients were predicted using the Chinese scoring system and compared to those predicted with the model for end-stage liver disease (MELD) score, MELD-Na score, and Child-Turcotte Pugh (CTP) score. Results: The Chinese scoring system was more effective at predicting the outcomes of survival and mortality than the MELD score. In the peak disease stage, the area under the Receiver Operating Characteristic curve for the Chinese scoring system was 0.954, significantly higher than that (0.896) for the MELD scoring system (P < 0.001). The positive prediction at 30, 90, and 180 days with the Chinese scoring system was 0.764 (95% confidence interval [CI]: 0.714-0.808), 0.731 (95% CI: 0.694-0.769), and 0.724 (95% CI: 0.679-0.765), also significantly higher than that with the MELD, MELD-Na, and CTP scores (P < 0.001). In addition, the Chinese scoring system was superior to the MELD, MELD-Na, and CTP scores (P < 0.001) at predicting the prognosis of patients with hepatitis B liver failure at both 30 and 180 days. Conclusion: The Chinese scoring system demonstrated superior performance to the three established scoring systems in assessing the severity and outcomes of hepatitis B liver failure in this cohort.